2004
DOI: 10.1111/j.1368-5031.2004.0117.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative clinical efficacy, onset and duration of action of levocetirizine and desloratadine for symptoms of seasonal allergic rhinitis in subjects evaluated in the Environmental Exposure Unit (EEU)

Abstract: The Environmental Exposure Unit, an indoor pollen challenge system to test anti-allergic medications, was used to compare the onset and duration of action and the efficacy of levocetirizine and desloratadine, two recently developed H1-antagonists. In this double-blind, placebo-controlled, parallel-group study, qualified subjects were randomised to once-daily levocetirizine 5 mg (n = 141), desloratadine 5 mg (n = 140) or placebo (n = 92) and exposed to ragweed pollen on two consecutive days (7 h and 6 h). Sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 45 publications
2
42
0
4
Order By: Relevance
“…56 -59 Recent publications have suggested that, at manufacturer's recommended doses, levocetirizine is less sedating than cetirizine 60 and desloratadine causes negligible somnolence. 49,61 However, it should be pointed out that "mean results" do not reveal everything as some patients may show considerable somnolence whereas others are unaffected.…”
Section: Unwanted Effects Somnolencementioning
confidence: 99%
“…56 -59 Recent publications have suggested that, at manufacturer's recommended doses, levocetirizine is less sedating than cetirizine 60 and desloratadine causes negligible somnolence. 49,61 However, it should be pointed out that "mean results" do not reveal everything as some patients may show considerable somnolence whereas others are unaffected.…”
Section: Unwanted Effects Somnolencementioning
confidence: 99%
“…[5] The latest-generation potent antihistamines such as desloratadine and levocetirizine have shown improved quality of life in allergic rhinitis studies. [6,7] Montelukast, a leukotriene receptor antagonist, significantly improves daytime and nighttime symptoms in patients with allergic rhinitis and is now an approved therapy for allergic rhinitis. [8] This study compares desloratadine monotherapy and combination montelukast with desloratadine on quality of life in allergic rhinitis.…”
mentioning
confidence: 99%
“…Of these, two studies were conducted in the Vienna Challenge Chamber (VCC) in a cross-over design and compared the efficacy of levocetirizine, loratadine/fexofenadine, and placebo28,29. Two other comparative studies were conducted in an environmental exposure unit (EEU) by Day et al 30,31. and in an environmental exposure chamber (EEC) by Patel and Patel 32 to evaluate the efficacy of levocetirizine with desloratadine or montelukast as a control medicine in studies with a parallel-group design.…”
Section: Discussionmentioning
confidence: 99%